Victim, reparation and criminal process: a projection from the expressive theories of punishment - Rámon Beltrán Calfurrapa (Revista Brasileira de Direito Processual Penal)
The present article tries to examine the most relevant aspects of the reparation of crime, in favor of the victim, under the assumption of the so-called “expressive theories of punishment”. For this, after explaining succinctly the importance and relevancy of the reparation in the field of criminal law and criminal procedure, will treat its political-criminal linkage based on the paradigms and essential postulates supported by such theories. In particular, it will analyze whether criminal reparation may or may not be understood under an expressive “telos” and, if so, whether its factual and communicative dimension can restore the normative deficit generated by the crime.